Analisis pengalaman pengguna pada E-Commerce selama promo Flash Sale dalam meningkatkan loyalitas pelanggan - Sumaryana , Fitriana Dewi; Hurriyati, Ratih; Dirgantari, Puspo Dewi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
This study aims to determine what factors influence customer satisfaction that can create customer loyalty itself. The type of research used in this study is explanatory research or explanatory research with a quantitative approach using survey methods. This study uses a multivariate analysis method (Partial Least Squares) which describes the relationship between exogenous variables, namely user experience during Flash Sale promos through customer satisfaction as an intervening variable to endogenous variables (customer loyalty). The number of samples used in this study were 260 e-commerce consumer respondents in the East Bandung area. The results of research from several aspects, namely usable, useful, valuable, and credible aspects have a positive influence in increasing e-commerce customer loyalty.